Behavioral Lateralization in Vertebrates Two Sides of the Same Coin - Csermely, Davide; Regolin, Lucia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Functional lateralization in the human brain was first identified in the classic observations by Broca in the 19th century. Only one hundred years later, however, research on this topic began anew, discovering that humans share brain lateralization not only with other mammals, but with other vertebrates and even invertebrates. Studies on lateralization have also received considerable attention in recent years due to their important evolutionary implications, becoming an important and flourishing field of investigation worldwide among ethnologists and psychologists. The chapters of this book concern the emergence and adaptive function of lateralization in several aspects of behavior for a wide range of vertebrate taxa. These studies span from how lateralization affects some aspects of fitness in fishes, or how it affects the predatory and the exploratory behavior of lizards, to navigation in the homing flights of pigeons, social learning in chicks, the influence of lateralization on the ontogeny process of chicks, and the similarity of manual lateralization (handedness) between humans and apes, our closest relatives.
Introduction -- The Effect of Sex and Early Environment on the Lateralization of the Rainbowfish Melanotaenia duboulayi -- Lateralization in Lizards: Evidence of Presence in Several Contexts -- Advantages of a Lateralized Brain for Reasoning about the Social World in Chicks -- Avian Visual Pseudoneglect: The Effect of Age and Sex on Visuospatial Side Biases -- Lateralized Social Learning in Chicks -- Organizational and Activational Effects of Prenatal Exposure to Testosterone on Lateralization in the Domestic Chicken (Gallus gallus domesticus) -- Navigating Through an Asymmetrical Brain: Lateralization and Homing in Pigeon -- The Right Hand Man: Manual Laterality and Language.
Keywords: Life sciences; Neurosciences; Animal behavior; Life Sciences; Behavioural Sciences; Neurosciences